Valoración económica del servicio de secuestro de CO2 en un bosque de colina baja de la concesión forestal N° 16-LOR-MAY/CON-MAD-2021-018, distrito de Mazán, Loreto. 2022 - Alván Vargas, Luis Felipe (2023)
This study calculated the cost of the CO2 sequestration service provided by a low hill forest in the Mazán district. The low hill forest of PC 3 in forest concession N° 16-LOR-MAY/CON-MAD-2021-018 was subjected to an evaluation of commercial species forest census data. According to the results, 10 299 trees, 50 commercial forest species and 20 botanical families were discovered. The economic value of CO2 sequestration is US$8 587 809,14, with the highest value species being Ormosia bopiensis (US$ 606,51/ha), Chrysophyllum argenteum (US$ 598,29/ha), Iryanthera grandis (US$ 595,92/ha) and Parkia ulei (US$ 495/ha). While the economic value of CO2 is lower in Apuleia leiocarpa (91,72 USD/ha), Diplotropis martiusii (91,03 USD/ha) and Dipteryx micrantha (88,39 USD/ha). The economic value of CO2 sequestration varies significantly (?=0,05) depending on the species. It is recommended to include the carbon sequestration services provided by these forests in the carbon market.